ANALISIS PEMAHAMAN GURU SEKOLAH DASAR DALAM MENGIMPLEMENTASIKAN KURIKULUM 2013 SE PEKANBARU - Sinta Nelia Utama; Otang Kurniaman; Hendri Marhadi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Absrak: This study aimed to describe the level of primary school teachers' understanding of the curriculum implementation se Pekanbaru, 2013. The subject of research is a primary school teacher with a total sample of 79 teachers. This research is descriptive quantitative research with survey method. Data showed that the level of understanding of elementary school teachers throughout Pekanbaru on the implementation of the curriculum in 2013 fall into the category simply by percentage of 57.97%. It can be seen from the number of acquisition pesentase any questions that represent indicators of understanding of curriculum implementation, 2013. The number of respondents who fall into the category very well is as much as 10 respondents with a percentage of 12.65%. Category well as much as 16 respondents with a percentage of 20.25%. Category quite as many as 22 respondents with a percentage of 27.85%. Less category as many as 31 respondents with a percentage of 39.24%. Indicators in this study there were four indkator, the first indicator that is about the objectives of the curriculum in 2013 with a percentage of 57.71% and category enough, the second indicator learning curriculum in 2013 and the percentage of 72.78% in both categories, the third indicator scientific approach with a percentage of 58.85 % and the category enough. The fourth indicator of authentic assessment with the percentage of 49.18% and category enough. This indicates that the level of understanding of elementary school teachers in curriculum implementation Pekanbaru se is simply the percentage of 57.97%. Conclusion of research is a primary school teacher Pekanbaru se should be given lessons and additional training on the implementation of the curriculum in 2013 to a systemic and sustainable.